THE EFFEC OF CONTEXTUAL TEACHING AND LEARNING METHOD IN WRITING ENGLISH PARAGRAPH AT ENGLISH DEPEARTMENT FKIP NOMMENSEN PEMATANGSIANTAR - Marnala Pangaribuan (Visi Sosial Humaniora, 2020)
This study is aim to know  the Effect of Contextual Teaching and Learning Method on the Students’ ability in Writing Paragraph at English Department of FKIP Nommensen Pematangsiantar. This research was an experimental study which conducted quantitative analysis. The population of this research was Group C and D students of English Department FKIP Nommensen Pematangsiantar Academic year 2018/2019. There were two classes. The samples of this research were taken from two classes. They were group C that consists of 45 students stated as the experimental class, and group D that consist of 25 students stated as the control class. After analyzing the data, the writer found that there was a significant effect of using Contextual Teaching and Learning Method to the students’ ability in writing paragraph. The Mean Score was 11,72 and the value of t-test was higher than t-table (t-test > t-table), 5,208 > 1,996. Ha (Alternative Hypothesis) was accepted and Ho (Null Hypothesis) was rejected. It can be concluded that by using contextual teaching and learning method, the students were encouraged to do writing paragraph in their daily life. The students have abilities to identify their weakness, accepted their mistakes and recognized their potential.